Ефективність збутової діяльності та місткість ринку плодово – ягідної продукції Півдня України - Колокольчикова, Ірина Володимирівна; Колокольчикова, Ирина Владимировна; Kolokolchykova, Iryna (My University, 2020)
UK: Одним зі шляхів успішного розвитку ринку плодово-ягідної продукції Півдня України є підвищення ефективності реалізаційної діяльності. Ці дії є стратегічними, тому що дають змогу оцінити збутову політику господарств-виробників, визначити характерні риси, притаманні лише цьому регіону, встановити місткість реального ринку продукції. Виявлення характерних тенденцій, які притаманні регіону, що досліджується, щодо товарної структури зерняткових та кісточкових плодів, а також ягід дає можливість виокремити регіональний аспект розвитку галузі. Аналіз тенденцій розвитку ринку плодів та ягід за реалізаційними показниками та оцінювання каналів збуту дають підстави говорити про міцність зв’язків з потенційними покупцями. Отримані результати є підставою висновків щодо недоліків та складності процесу збуту задля пошуку шляхів їх вирішення. EN: The article is devoted to research of the market of fruit and berry products in the South of Ukraine on the issues of product sales, market capacity and analysis of the situation that has developed. The volume of sales of fruits and berries in Ukraine as a whole, as well as in its southern regions, namely in Zaporozhe, Mykolaiv, Odessa and Kherson. The analysis of the level of marketability of products in the context of agricultural enterprises and households that represent the small business sector. An explanation is given for the value of the level of profitability of sales. The result of the study is the following. Regional features of the implementation activities of farms in the South of Ukraine in the context of seed and stone fruits that are being sold are established. The analysis revealed that the region reflects trends in General relative to the volume of sales of grain fruits, namely apples. However, among stone fruits, the production volumes of such types as cherries, cherries, peaches and apricots, give grounds to conclude that the best position of the South of Ukraine among other natural zones. One of the reasons for this state is the natural and climatic potential of this growing area. The market capacity of this regional segment is estimated and it is found that there is a tendency to decrease the size of the indicator. Comparing the level of marketability of fruits and berries among agricultural enterprises and households of the population, leads to the conclusion that the best position for representatives of medium-sized businesses. Farms of the population have a low level of marketability of products due to the fact that most of them are not commercial in the form of management. The products are produced by the population for their own consumption, and only a part of it is sold as leftovers. Also, the reason for the low indicator is the lack of permanent connections with potential buyers and the inability to enter sales markets. There are several channels for selling products in Ukraine and in the southern part of the country. The reasons for reducing the profitability of implementation activities by regions are determined. As a comprehensive solution to complex issues in the market of fruit and berry products in the South of Ukraine is the development of a regional concept of development and implementation of its components in order to improve performance indicators.
Efficiency of sales activity and market capacity of fruit and berry products in the South of Ukraine
Keywords: ефективність; збут; ринок; місткість ринку; рівень рентабельності; потенційні покупці; efficiency; sales; market; market capacity; level of profitability; potential buyers